2020
DOI: 10.1097/sla.0000000000002985
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nutritional Index, Tumor-infiltrating Lymphocytes, and Prognosis in Patients with Esophageal Cancer

Abstract: Objective: To determine whether prognostic nutritional index (PNI) affects clinical outcome through local immunity in esophageal cancers. Background: PNI is an indicator of nutritional status and systemic immune competence, and has attracted attention as a prognostic biomarker. Tumor-infiltrating lymphocytes (TILs) are a specific histological feature of human cancers, reflecting an individual's immunological tumor response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
236
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 283 publications
(281 citation statements)
references
References 35 publications
6
236
2
1
Order By: Relevance
“…The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated as ANC/ALC and platelet count/ALC, respectively. In addition, we calculated the prognostic nutritional index (PNI), which is associated with the survival outcome and nutritional status of cancer patients, including esophageal cancer patients [24,25]. PNI was calculated as (10 × albumin [g/dL] + 0.005 × ALC) [26].…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated as ANC/ALC and platelet count/ALC, respectively. In addition, we calculated the prognostic nutritional index (PNI), which is associated with the survival outcome and nutritional status of cancer patients, including esophageal cancer patients [24,25]. PNI was calculated as (10 × albumin [g/dL] + 0.005 × ALC) [26].…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…[16][17][18] The status of nutrition is also closely associated with postoperative complications and the clinical outcomes of patients with various solid tumors. Recently, many indicators containing nutritional and inflammatory variables have been found to play a role in predicting the prognoses for cancer patients, such as those with colorectal cancer, 19 esophageal cancer, 20 and so on. The concept of the prognostic nutritional index (PNI) was first proposed by Buzby et al 21 to evaluate the risk of gastrointestinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have shown that PNI has been identified as a novel prognostic parameter. Lower PNI was significantly associated with inferior survival in nasopharyngeal carcinoma, hepatocellular carcinoma, esophageal cancer, renal cell carcinoma, and ovarian cancer (Du et al, 2015; Feng et al, 2018; Kang et al, 2017; Okadome et al, 2018; Pinato, North, & Sharma, 2012). However, it is noteworthy that the values of this prognostic biomarker considerably varied in diverse cancer contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that it reflects immunonutritional status and systemic inflammatory reaction with more accuracy than other variables (Morgan et al, 2011). Furthermore, PNI has been reported to be a powerful and independent prognostic factor in human cancers such as colorectal cancer, gastric cancer, lung cancer, and esophageal cancer (Migita et al, 2013; Mori et al, 2015; Noh et al, 2017; Okadome et al, 2018). However, the prognostic significance of PNI in OSCC remains largely underexplored.…”
Section: Introductionmentioning
confidence: 99%